2017
DOI: 10.1090/proc/13550
|View full text |Cite
|
Sign up to set email alerts
|

Finite groups and their coprime automorphisms

Abstract: Let p p be a prime and A A a finite group of exponent p p acting by automorphisms on a finite p ′ p’ -group G G . Assume that A A has order at least p 3 p^3 and C G ( a ) C_G(a) is nilpotent of class at most c c for any a ∈ A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Subsequently the above result was extended to the case where A is not necessarily abelian. Namely, it was shown in [2] that if A is a finite group of prime exponent q and order at least q 3 acting on a finite q ′ -group G in such a manner that C G (a) is nilpotent of class at most c for any a ∈ A # , then G is nilpotent with class bounded solely in terms of c and q. Many other results illustrating the influence of centralizers of automorphisms on the structure of G can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently the above result was extended to the case where A is not necessarily abelian. Namely, it was shown in [2] that if A is a finite group of prime exponent q and order at least q 3 acting on a finite q ′ -group G in such a manner that C G (a) is nilpotent of class at most c for any a ∈ A # , then G is nilpotent with class bounded solely in terms of c and q. Many other results illustrating the influence of centralizers of automorphisms on the structure of G can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown in [13] that the assumption that A is abelian is actually superfluous in the above result. That is, the result holds for any group A of prime exponent.…”
Section: Proof Of Theorem A3mentioning
confidence: 93%
“…only". In the recent article [3] the above result was extended to the case where A is not necessarily abelian. Namely, it was shown that if A is a finite group of prime exponent q and order at least q 3 acting on a finite q ′ -group G in such a manner that C G (a) is nilpotent of class at most c for any a ∈ A # , then G is nilpotent with class bounded solely in terms of c and q.…”
Section: Introductionmentioning
confidence: 93%
“…# . An alternative way of expressing this is to say that C G (B) is generated by the subgroups C G (A i ) (see for example [3,Lemma 2.3]) . Now, for any subgroup…”
Section: Preliminariesmentioning
confidence: 99%